Compression Behavior of FFF Printed Parts Obtained by Varying Layer Height and Infill Percentage - Zisopol, D. G.; Nae, I.; Portoaca, A. I. (Engineering, Technology & Applied Science Research, 2022)
In this research, two polymeric materials, PLA-(polylactic acid) and ABS (acrylonitrile butadiene styrene) were used to 3D print compression samples at 3 layer heights (0.10, 0.15, and 0.20mm) with 3 infill percentages (50%, 75%, 100%). In order to determine the material’s behavior under applied crushing loads, 135 samples were fabricated and tested. The built compression PLA specimens were subjected to common annealing treatment just above glass transition temperature and it was proved that the set of 45 samples exhibited higher resistance to the compressive load applied to the material before fracturing by an average of 9.20%.